Histological characteristics, cell wall hydrolytic enzyme activity, and transcriptome analysis with seed shattering of Stylosanthes accessions - Li, Xinyong; Zhang, Jingwen; Zhang, Jingxue; Sheng, Wei; Huang, Rui; Dong, Rongshu; Ding, Xipeng; Liu, Pandao; Liu, Guodao (Frontiers in Plant Science, 2022)
Stylo (Stylosanthes spp.) is an annual or perennial legume forages that is widely grown as forage and cover crops in tropical and subtropical regions. Because of serious seed shattering, the seed yield of stylo is very low, and it is difficult to seed production. Therefore, we first synthesize morphological, histological characteristic analyses, physiochemical and transcriptome analysis to show the seed shattering mechanism on stylo. We found that the phenomenon of seed shattering was common among stylo accessions. In generally, the stylo germplasm with shorter lobules and thicker stems had a lower seed shattering rate and higher seed weight. The seed and seed stalk joint is the abscission zone in the stylo. Multiplex histology and hydrolytic enzyme activity analysis showed the tearing of the abscission zone occurs due to intense enzymatic degradation of the polygalacturonase and cellulase in seed shattering-susceptible accession TF0275. Furthermore, the 26 genes were associated with capacity of stylo to shed its seeds. This study provides valuable insights for future mechanistic studies of seed shattering in stylo.